Pengaruh Social Media Marketing, Store Atmosphere dan Electronic Word of Mouth terhadap Customer Loyalty Starbucks Kota Samarinda - Fatma Azizah; Muhammad Fikry Aransyah (Universitas Batanghari, 2023)
This study aims to determine the effect social media marketing, store atmosphere and electronic word of mouth to customer loyalty Starbucks City of Samarinda. The sample selection technique uses purposive sampling with a sample obtained by 100 respondents. Data collection was carried out by distributing questionnaires at all Starbucks outlets in Samarinda City. The data that has been collected is processed using the SmartPLS 3.2.9 analysis tool with the SEM method. The results of this study indicate that there is a significant effect on store atmosphere to customer loyalty, electronic word of mouth have a significant effect on customer loyalty. Whereas, Social media marketing no significant effect on customer loyalty.